THE RARE Z-]J/PSI(UPSILON)+X DECAYS IN SU(2)XU(1)XU(1) GAUGE-THEORIES - AKKUS, B; CETIN, Y; SILAHTAROGLU, E; BAHADIROGLU, G (EDITRICE COMPOSITORI BOLOGNA, 1994)
In the framework of the SU(2) x U(1) x U(1) gauge model the rare decays Z --> J/psi(gamma) + X (where X is the light gauge boson corresponding to the extra U(1) group) are investigated. Using the model of independent restrictions to the coupling constant and mass of X-boson, it is shown that, in some region of parameters, these decay rates (greater-than-or-equal-to 10 keV) can be measurable in LEP with high luminosity.
Keywords: Physics